2018
DOI: 10.1002/ls.1414
|View full text |Cite
|
Sign up to set email alerts
|

Combined experimental and multiphase computational fluid dynamics analysis of surface textured journal bearings in mixed regime of lubrication

Abstract: This paper investigates the effect of surface texturing in a partial pad journal bearing through a series of controlled experiments at operating conditions, promoting mixed or boundary regimes of lubrication. Improvements to load carrying capacity are observed under certain operating conditions. A comprehensive À Á 2 ; Δ ij , Kronecker delta; ε, Eccentricity ratio; η, Lubricant dynamic viscosity; θ, Circumferential direction in bearing; λ, Stribeck oil film parameter; μ, Pressure coefficient for boundary shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Gu et al [16] presented a mixed lubrication model to analyze the performance of the journal bearing with groove textures operating from mixed to hydrodynamic lubrication regime, and the influences of fluid piezoviscosity and non-Newtonian behaviors are also taken into consideration. Morris et al [17] investigated the effects of textured surface in a partial pad journal bearing by experiments. Their results showed the effective load bearing region is extended due to micro-hydrodynamic effect, which can improve the load carrying capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Gu et al [16] presented a mixed lubrication model to analyze the performance of the journal bearing with groove textures operating from mixed to hydrodynamic lubrication regime, and the influences of fluid piezoviscosity and non-Newtonian behaviors are also taken into consideration. Morris et al [17] investigated the effects of textured surface in a partial pad journal bearing by experiments. Their results showed the effective load bearing region is extended due to micro-hydrodynamic effect, which can improve the load carrying capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Fu et al [2] used the mass conserving cavitation model to simulate the cavitation regions, the results of the model are validated by the experimental data from the literature. Morris et al [3] showed that improved conditions with a textured journal, delaying the effect of lubricant rupture, thus extending the effective region of bearing load. Poddar et al [4] got a clearer picture of the film by filming the moment of the film, using vibration and sound technology to monitor the formation of cavitation.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the pioneering study of Hamilton et al [1], the positive influences of surface texturing have been highlighted in lubricated contact. Recent experimental results in this area [2][3][4] revealed that significant amelioration in lubrication performance can be obtained by surface texturing. According to Morris et al [2], promoting the micro-hydrodynamic effect could delay the influence of lubricant rupture and consequently the effective load bearing region could be extended.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental results in this area [2][3][4] revealed that significant amelioration in lubrication performance can be obtained by surface texturing. According to Morris et al [2], promoting the micro-hydrodynamic effect could delay the influence of lubricant rupture and consequently the effective load bearing region could be extended. By introducing the texture pattern on the whole of the bearing shell circumference, substantial friction reduction (approximately 18%) was achieved when compared to the smooth (untextured) reference as reported by Vlădescu et al [3].…”
Section: Introductionmentioning
confidence: 99%